Big Data a game changer for insurance industry - Sood, Kiran; Kumar Dhanaraj, Rajesh; Balusamy, Balamurugan; Grima, Simon; Maheshwari, R. Uma (Emerald Publishing, 2022)
CONTENTS: 1: Use of Wearable and Health Applications in Insurance Industry Using Internet of Things and Big Data 2: Emerging Technologies of Big Data in the Insurance Market 3: Adoption of Internet of Things and Services in the Indian Insurance Industry 4: Emerging Technologies in Insurance Sector: Evidence from Scientific Literature 5: Predictive Performance of Indian Insurance Industry Using Artificial Neural Network (ANN) and Support Vector Machine (SVM): A Comparative Study 6: Blockchain Technology as an Emerging Technology in the Insurance Market 7: Crowdsourcing, Insurance and Analytics: The Trio of Insurance Future 8: Big Data in Insurance Innovation 9: Big Data Analytics Application and Enhanced FDI Prospects for the Insurance Sector 10: The Use of Big Data in the Insurance Industry Innovations in China 11: New Developments in Banking Sector and Impact: Covid-19 12: Foreign Direct Investment Impact and Effect on the Indian Insurance Sector: Major Key Drivers 13: Big Data Analytics - Tools and Techniques - Application in the Insurance Sector 14: Revamping Indian Non-Life Insurance Industry with a Trusted Network: Blockchain Technology 15: Digital Financial Inclusion 16: Perceived Effectiveness of Digital Transformation and InsurTech Use in Malta: A Study in the Context of the European Unions Green Deal 17: The General Data Protection Regulation (GDPR) for Risk Mitigation in the Insurance Industry 18: Cybersecurity Law-based Insurance Market
Keywords: Big Data; Aufsatzsammlung